2007
DOI: 10.1021/jo0622532
|View full text |Cite
|
Sign up to set email alerts
|

Thiopyran Route to Polypropionates:  Exploiting and Overcoming Double Stereodifferentiation and Mutual Kinetic Enantioselection in Aldol Couplings of Chiral Fragments

Abstract: The aldol reaction of tetrahydro-4H-thiopyranone with 1,4-dioxa-8-thiaspiro[4.5]decane-6-carboxaldehyde (I) gives four possible diastereomeric adducts (II). Aldol reactions of I with each of the diastereomers of II and their corresponding methoxymethyl ethers III via the Ti enolates were investigated. Using racemic reactants, reactions with II proceeded with high levels of mutual kinetic enantioselection (MKE) and double stereodifferentiation (DS) to give one of the eight possible bisaldol adducts. Similar rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…During the last decade, the essential elements of this strategy were explored extensively in the Ward group (Scheme 1.1). Different approaches such as the iterative aldol reaction of tetrahydro-4H-thiopyran-4-one 7 with carboxaldehyde 6 4,5 or a simultaneous aldol reaction of dialdehyde 8 with tetrahydro-4H-thiopyran-4-one 7 were developed. 6 All these efforts provided rapid access to tetra and hexapropionate synthons.…”
Section: The Thiopyran Route To Polypropionatesmentioning
confidence: 99%
See 3 more Smart Citations
“…During the last decade, the essential elements of this strategy were explored extensively in the Ward group (Scheme 1.1). Different approaches such as the iterative aldol reaction of tetrahydro-4H-thiopyran-4-one 7 with carboxaldehyde 6 4,5 or a simultaneous aldol reaction of dialdehyde 8 with tetrahydro-4H-thiopyran-4-one 7 were developed. 6 All these efforts provided rapid access to tetra and hexapropionate synthons.…”
Section: The Thiopyran Route To Polypropionatesmentioning
confidence: 99%
“…Previous results demonstrated that all 20 possible diastereomers could be obtained through iterative two-directional aldol reactions or simultaneous aldol reaction of tetrahydro-4H-thiopyran-4-one 7 and dialdehyde 8 (Scheme 1.1). 4,6,7 Controlling the stereoselectivity of these aldol couplings is an ongoing objective in the Ward group. To date, the thiopyran route has been used successfully in total syntheses of several polypropionate natural products such as serricornin, …”
Section: The Thiopyran Route To Polypropionatesmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5-trans selectivity) of a protecting group on the C-1' OH group. 45 In addition, the diastereoface selectivity of the aldehyde 173 was shown to be highly Felkin selective; i.e., leading to products with a 1",6"-syn relative configuration. 45 In this research, the development of conditions to switch the relative topicity (5,1"-anti or 5,1"-syn)…”
Section: The Thiopyran Route To Polypropionates: Design Of Aldol Reacmentioning
confidence: 99%